The power of imagination (Journal of Parents and Teachers, 2025)
‘Only through imagination is it possible to structure the idea of what we can be.’ That is how important imagination is. However, there is inevitably a conflict between fantasy and reality, where reality exists and fantasy does not. But then, do dreams and feelings not exist because they cannot be seen? The possibilities of where imagination can take us through creativity, personal balance, memory and escape are endless. In turn, imagination is fuelled by play, feelings, life experiences and poetic language. Children are able to adapt to reality through imagination, which is why it is very important to let them express their ideas freely, so that they can form their own thoughts and, from there, build their own personality, because, as Piaget says, the construction of the imagination is deeply linked to the construction of the person.
Keywords: imagination, reality, fantasy, creativity, freedom